Legal Perspectives on al-Waṣiyyah and al-Mīrāth: A Comparative Analysis of Imami and Hanafi Jurisprudence - Huseen, Walaa Ali (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
The term “will” (al-Waṣiyyah) is an ancient term, but in some periods it was associated with injustice and unfairness. The head of the household had the right to dispose of the will without restrictions, which could allow him to make a will to a stranger and deprive his children of their inheritance rights (al-Mīrāth). In pre-Islamic times, Arabs made wills to strangers out of pride and boasting, leaving relatives in poverty and need. With the advent of Islam, the concept of the will was redefined to be based on truth and justice. Before the inheritance law was enacted, wealthy individuals were required to make a will to their parents and relatives. Consequently, in early Islam, a will became obligatory for all of a person's property for the benefit of their parents and relatives. The rulings on wills differ from one school of thought to another, depending on the issues involved, such as conflicting wills, impediments to inheritance, and the ruling on the time of establishing a will.